Analysis of Students Mathematical Reasoning in Solving Cuboid and Cube Problems Based on Learning Styles. - Ayu Wanlin, Agnes Putri; Parta, I Nengah; Rahardjo, Swasono (Universitas Suryakancana, 2025)
Mathematical reasoning ability is an important skill that students must have in the process of learning mathematics. This skill allows students to develop logical, analytical, systematic, critical, and creative thinking patterns. Based on this, the researcher examined the mathematical reasoning ability of grade VII students at SMP Negeri 2 Pakisaji in solving story problems about blocks and cubes. This study is entitled